GAMBARAN DARAH IKAN NILA (Oreochromis niloticus) YANG DIBERI PAKAN TERFORTIFIKASI EKSTRAK CAIR DAUN SALAM (Syzygium polyanthum) - Wahyu Dwi Putranto; Denny Syaputra; Eva Prasetiyono (Jurusan Akuakultur, Universitas Bangka Belitung, 2019)
Tilapia (Oreochromis niloticus) is populer as resistant fish to environmental changes. Cultivating fish with a high stocking density can cause a decrease in water quality. It has an impact on susceptibility to disease due to decreased water quality. Immunostimulants from Phyto-pharmacy are needed to improve the non-specific immune system of fish from natural ingredients. Bay leaves (Syzigium polyanthum) have the potential to be used as an immunostimulant in fish. This study aimed to evaluate the extract of Salam leaves fortified in feed against the blood profile of Tilapia. The research was carried out in April - May 2018 using a completely randomized design (CRD) with 4 treatments and 3 replications. Salam leaf extract through feed affects the increase of leucocytes and blood erythrocytes of tilapia but does not affect hemoglobin levels and hematocrit levels. Doses of 2x10-2 g mL-1 increased fish blood leukocytes on day 21st to be the best treatment in this study.